DAMPAK PROGRAM MAKAN BERGIZI GRATIS (MBG) TERHADAP KONSENTRASI SISWA SEKOLAH DASAR DALAM KEGIATAN BELAJAR (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
In Indonesia, malnutrition remains a serious public health issue, with many elementary school children experiencing inadequate nutritional intake, negatively impacting their concentration, motivation, and academic achievement. This study aims to analyze the impact of the MBG Program on elementary school students' concentration during learning activities. This study used a descriptive qualitative approach with data collection techniques through in-depth interviews, participant observation, and documentation. Research informants included students, classroom teachers, parents, and school officials directly involved in the implementation of the MBG program. The results showed that the implementation of the MBG Program contributed to increased student concentration, as indicated by increased learning focus duration and reduced distractive behavior in class. In addition, MBG also increased student motivation and active participation in the learning process. Support from teachers, parents, and school officials strengthened the program's effectiveness in creating a more conducive learning atmosphere. Overall, the MBG Program has proven to play a significant role in supporting students' learning readiness and improving the quality of the learning process in elementary schools.